Saturday, 16 JUNE 2018 2018
DOI: 10.1136/annrheumdis-2018-eular.3106
|View full text |Cite
|
Sign up to set email alerts
|

SAT0318 Do patients in remission in psoriatic arthritis, have less fatigue? and does this depend on the definition of remission? an analysis of 304 patients

Abstract: BackgroundFatigue is a critical element of life impact for patients with Psoriatic Arthritis (PsA) and is not considered in remission definitions. In PsA, remission can be defined using composite scores (Minimal Disease Activity (MDA), Disease Activity in PSoriatic Arthritis (DAPSA)≤4), Patient Acceptable Symptom State (PASS), Patient Global Assessment (PGA)(for example ≤1/10), or as a single for remission item.ObjectivesTo explore the relationship between fatigue and remission in PsA, when using different def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
(1 reference statement)
1
3
0
Order By: Relevance
“…In this sense, our findings are quite consistent with those of the recently published ReFlap (Remission/Flare in PsA) study [16]. In ReFlap, adults with physician-confirmed PsA and >2 years of disease duration in 14 countries were included.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In this sense, our findings are quite consistent with those of the recently published ReFlap (Remission/Flare in PsA) study [16]. In ReFlap, adults with physician-confirmed PsA and >2 years of disease duration in 14 countries were included.…”
Section: Resultssupporting
confidence: 91%
“…In this study, DAPSA-based remission/low disease activity (LDA) performed better than VLDA/MDA to detect patient defined remission or remission/LDA. Further, physician-perceived remission/LDA using a single question was frequent (67.6%) but performed poorly against other definitions [16].…”
Section: Resultsmentioning
confidence: 93%
“…15 In total, 5 included studies were retrospective observational studies, [24][25][26][27][28] and 9 were cross-sectional studies. [29][30][31][32][33][34][35][36][37] Only 1 study was reported as a qualitative research study 38 and, finally, 1 study was reported as a population-based cohort study. 39 Population size varied greatly across the included studies, from 108 patients 14 to 8677 patients 25 (Supplementary Table S7, available with the online version of this article).…”
Section: Resultsmentioning
confidence: 99%
“…PsA-specific measures may represent a better way to illustrate sex-specific differences in the experience of the disease; however, they were employed only in 6 included studies. [18][19][20]29,30,36 Further, it is important to consider that although PROs can capture levels of self-reported physical function, the source of pain or reason for the functional impairment cannot be known in detail. In order to better capture the impact of disease on patients and pursue the most relevant improvements in clinical outcomes, qualitative patient interviews might be a useful way to explore sex-specific differences in PsA.…”
Section: Discussionmentioning
confidence: 99%